India and Southeast Asia : Towards Security Convergence - Devare, Sudhir (Book collections on Project MUSE., 2006)
There is a growing dialogue between India and Southeast Asia. From a marginal relationship during the Cold War days to the participation of India at the East Asia summit in December 2005 has been a long journey. In the context of the geopolitical situation in the Asia-Pacific in the post-September 11 period, the security dimension between India and Southeast Asia cannot be overemphasized. With the continued U.S. preponderance in the region and China's phenomenal rise, the countries of Southeast Asia and India have an opportunity to evolve a co-operative relationship not only with one another, but also with the major powers of the region. This book examines the areas of comprehensive security and the growing understanding between India and Southeast Asia where there is less divergence and greater convergence. The author argues that India-Southeast Asia security convergence is not and should not be aimed at any particular country. On an optimistic note he concludes that such convergence will contribute to creating harmony among the major powers of Asia to make the twenty-first century the "Asian century".--